Multi-omics analysis identifies Sphingomonas and specific metabolites as key biomarkers in elderly Chinese patients with coronary heart disease - Zhou, Xiaoshan; Zhang, Tianlong; Jia, Sixiang; Xia, Shudong (Frontiers in Microbiology, 2025)
BackgroundAbnormal component changes of gut microbiota are related to the pathogenesis and progression of coronary heart disease (CHD), and gut microbiota-derived metabolites are key factors in host-microbiome interactions. This study aimed to explore the key gut microbiota and metabolites, as well as their relationships in CHD.MethodsFeces samples and blood samples were collected from CHD patients and healthy controls. Then, the obtained feces samples were sent for 16s rRNA gene sequencing, and the blood samples were submitted for metabolomics analysis. Finally, conjoint analysis of 16s rRNA gene sequencing and metabolomics data was performed.ResultsAfter sequencing, there were no significant differences in Chao 1, observed species, Simpson, Shannon, Pielou’s evenness and Faith’s PD between the CHD patients and controls. At phylum level, the dominant phyla were Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria. At genus level, the abundance of Sphingomonas, Prevotella, Streptococcus, Desulfovibrio, and Shigella was relatively higher in CHD patients; whereas Roseburia, Corprococcus, and Bifidobacterium was relatively lower. Randomforest analysis showed that Sphingomonas was more important for CHD. Through metabolomic analysis, a total of 155 differential metabolites were identified, and were enriched in many signaling pathways. Additionally, the AUC of the conjoint analysis (0.908) was higher than that of gut microbiota species (0.742).ConclusionIn CHD patients, the intestinal flora was disordered, as well as Sphingomonas and the identified differential metabolites may serve as was candidate biomarkers for CHD occurrence and progression.